Influence Research for Softening and Swelling of Weakly Cemented Soft Rock on the Stability of Surrounding Rock in Roadway - Yan Li; Chao Ma; Lianying Zhang; Bing Li (Geofluids)
In order to study the influence of the softening and swelling of weakly cemented soft rock on the stability of roadway surrounding rock, based on the background of the general return airway in the south wing of Yuwu coal mine, 4 different schemes are designed according to whether the softening or swelling effect of weak cemented soft rock is considered. Based on the numerical simulation program, FLAC3D was used to analyze the distribution characteristics of the shear stress, displacement, and plastic zone of the surrounding rock of the roadway under these 4 designs. On this basis, in view of the geological conditions of the roadway, a new type of “grouting + anchor cable mesh + bottom arch” combined support plan is proposed. The research results show that, under the conventional anchor-net-cable-spraying support scheme, the surrounding rock of the roadway can remain stable without considering the softening and expansion of the weakly cemented soft rock in contact with water and its maximum displacement and plastic zone depth are only 66.9 mm and 2.8 m. When considering the softening and swelling of weakly cemented soft rock roadways, due to the synergistic effect of the two, the maximum displacement of the surrounding rock of the roadway and the depth of the plastic zone will reach 517.4 mm and 6.7 m, respectively, which will continue to increase with excavating along the roadway and lead to ultimately destabilization and destruction. After adopting the combined support of “grouting + anchor cable mesh + bottom arch,” the maximum displacement of the surrounding rock of the roadway and the depth of the plastic zone will be reduced by 77.1% ∼ 92.0% and 18.7% ∼ 72.4%, respectively, and they will basically remain stable after excavation of 5 days.